Prarancangan Pabrik Disodium Phosphate Heptahydrate Dari Sodium Carbonate Dan Phosphoric Acid Kapasitas 55.000 Ton/ Tahun - Choirul Wibowo, Alwafi, Kusmiyati, S.T., M.T., P.hD, Kun Harismah, Ph.D (2016)
Disodium phosphate heptahydrate is widely used in the chemical industry as a raw material in the manufacture of detergents, as plasticizers (water treatment), for textile dyes, leather tanning and materials for the paper industry. To meet domestic demand still remains to be imported from abroad and their export opportunities that are still open, disodium phosphate heptahydrate designed plant with a capacity of 55,000 tons/year with H3PO4 raw materials 3161.9136 kg/h and Na2CO3 7468.1387 kg/hour. The factory is planned to stand in the Industrial Area Gresik, East Java in 2017 with an area of 45.160m2. The total amount of water needs of 143,500 kg/hour, the water extracted from the river Bengawan Solo. Total steam requirement is 8480.8250 kg/h, used boilers 16,566,328.173 capacity Btu/hr. The fuel used is diesel plant of 20.621 m3/hour. The electricity needs of the plant amounted to 2200 kW. Electricity is obtained from the PLN and generator. Compressed air is obtained from two compressor with a capacity each of 100 m3/h. From the results of the economic analysis is obtained, Return on Investment (ROI) before and after tax of 45.41% and 31.79%, Pay OutTime (POT) before and after tax for 1.81 years and 2.39 years, Break-even Point (BEP) 50%, and Shutdown Point (SDP) 37.37%. While the Discounted Cash Flow (DCF) of 29.80%. So in terms of economic, disodium phosphate heptahydrate plant is worth considering establishment. Keyword: disodium phosphate heptahydrate, H3PO4, Na2CO3.